Kålgallmygga, Contarinia nasturtii Kieffer - Andersson, Stina (2006)
The purpose of this paper is to examine what problems cabbage growers have with the Swede Midge. The last few years the Swede Midge, Contarinia nasturtii, has become a larger problem for cabbage growers in several countries in Europe as well as in Sweden. In Canada the problems are so severe that the midge is classified as a quarantine pest and therefore certain rules have to be followed. I have collected facts of the biology, host plants and reproduction of the Swede Midge, as well as the growers experiences and the occurrence of the midge in Canada, Europe and Sweden. The Swede Midge is hard to control because of its short life cycle and the larvae are protected between the heartleaves of the plant. When the larva feeds on the growth point the plant becomes distorted, in some cases several heads develop or none at all. When the midge infests spring rape its flower buds become undeveloped and rosette like. By severe infestations in spring rape the fields can re-flower later during the season. In Sweden the midge has two to three generations per year. The larvae overwinter in the soil for about 1-2 years. I have counted midges caught in the pheromone traps, placed in fields of winter wheat, spring rape and cabbage by Växtskyddscentralen, Alnarp, 2005, to get a picture of the generations and reproduction of the Swede Midge. The results show that a large amount of midges overwinter in the spring rape fields and hatch the following year. Then the midges fly to new hostplants and start a new generation. If there are cabbage fields nearby, the next generation of the Swede Midge can cause severe damage. An investigation was made in the 1970's in Skåne and Blekinge, which showed that the infestations were severe. Already then it was established that a large increase of the midge population in spring rape could lead to huge consequences for the cabbage grower. The pheromone traps in the cabbage fields show that if cabbage is grown year after year or on a field nearby, the population is kept alive. The chemical control should be directed towards the adult midges. However, today there is no good method of actually knowing when the midge flies. The pheromon traps have made it possible to start the development of a monitoring system. Research and trials are in progress to optimize the pesticide treatment to the flight peaks and to prevent egg-laying. Still there are some preventive measures to be taken, such as crop rotation, controlling weeds and field selection. Except developing a reliable monitoring system, further knowledge of the overwintering of the larvae in the soil and of its natural enemies is needed. Together with the preventive measures it is possible to find new ways of controlling the Swede Midge and hopefully to reduce the use of pesticides.